2007
DOI: 10.1038/ncpcardio0944
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous closure of a patent foramen ovale in left-sided carcinoid heart disease

Abstract: Percutaneous transcatheter closure of the patent foramen ovale.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 14 publications
0
7
0
Order By: Relevance
“…[6] According to the result of our previous prospective study, all patients with PFO closure presented a reduction of symptoms, but unfortunately, this percutaneous closure can't protect the left heart from serotonin, because of residual right-to-left atrial shunt. Few case reports of PFO closure in CHD have been recently published [7,8] and we believe that this procedure could be particularly of interest in CHD patients with symptomatic PFO but without any planned valvular surgery.…”
Section: Discussionmentioning
confidence: 96%
“…[6] According to the result of our previous prospective study, all patients with PFO closure presented a reduction of symptoms, but unfortunately, this percutaneous closure can't protect the left heart from serotonin, because of residual right-to-left atrial shunt. Few case reports of PFO closure in CHD have been recently published [7,8] and we believe that this procedure could be particularly of interest in CHD patients with symptomatic PFO but without any planned valvular surgery.…”
Section: Discussionmentioning
confidence: 96%
“…We report a case of a carcinoid heart disease with a right to left shunt through a PFO resulting in dyspnea and worsening hypoxia that was successfully treated by percutaneous PFO closure that resulted in normalized oxygen saturation, symptomatic relief, and improved quality of life. To our knowledge, there were only five similar reported cases of flow-driven R-L shunting due to the tricuspid regurgitation jet directing deoxygenated blood towards the PFO, resulting in hypoxemia and dyspnea [8,[10][11][12][13][14].…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, there have been three such cases reported in the literature ( Table 2 ). Chaudhari et al 12 reported a case of a patient with carcinoid heart disease causing R-L shunt via flow-driven mechanism due to external compression of the vena cava by tumour mass directing caval blood towards the PFO. The other two cases were reported by Yang et al .…”
Section: Discussionmentioning
confidence: 99%